Homocysteine as a Risk Factor for Restenosis after Coronary Angioplasty - Morita, Hiroyuki; Kurihara, Hiroki; Kuwaki, Tomoyuki; Hamada, Chikuma; Kitaoka, Masao; Suzuki, Shin; Yazaki, Yoshio; Nagai, Ryozo (Thrombosis and Haemostasis, 2000)
We examined the relationship between plasma homocysteine levels and restenosis after PTCA (Percutaneous transluminal coronary angioplasty) to investigate whether plasma homocysteine levels can be a predictor of restenosis after PTCA. One hundred and twelve male patients who have undergone a successful elective PTCA were consecutively enrolled and plasma homocysteine levels were measured at the time of follow-up angiography. Plasma homocysteine levels in patients with restenosis were significantly higher than those in patients without restenosis (15.0 ± 3.9 vs. 13 ± 2.9 µmol/L; P = 0.011). The difference was augmented when diabetic patients were selectively studied. The comparison between restenosis group and non-restenosis group indicated the threshold effect of hyperhomocysteinemia. These results suggest that plasma homocysteine is a potential risk factor of restenosis after PTCA, and therapeutic strategy targeted against hyperhomocysteinemia may be beneficial for preventing restenosis.
Keywords: Homocysteine; PTCA; restenosis; risk factor